Atrial Fibrillation After mRNA-1273 SARS-CoV-2 Vaccination: Case Report with Literature Review - Chen CY; Hsieh MT; Wei CT; Lin CW (Dove Medical Press, 2023)
Chao-Yang Chen,1 Ming-Ta Hsieh,1,2 Chen-Ting Wei,1 Chi-Wei Lin1,3 1Department of Family Medicine and Community Medicine, E-Da Hospital, Kaohsiung City, Taiwan; 2Department of Nursing, College of Medicine, I-Shou University, Kaohsiung City, Taiwan; 3School of Medicine for International Students, College of Medicine, I-Shou University, Kaohsiung City, TaiwanCorrespondence: Ming-Ta Hsieh, Department of Family Medicine and Community Medicine, E-Da Hospital, Kaohsiung City, Taiwan; Department of Nursing, College of Medicine, I-Shou University, No. 1, Yida Road, Jiao-Su Village, Yan-Chao District, Kaohsiung City, 824005, Taiwan, Email kaplan210@yahoo.com.twImportance: COVID-19 vaccination has been associated with various adverse outcomes. Although studies have reported cases of arrhythmia after COVID-19 vaccination, the precise underlying mechanism remains to be elucidated.Objective: Here, we report the case of a patient who developed atrial fibrillation after receiving the mRNA-1273 vaccine and describe our findings in light of relevant cases in the literature.Design, Setting, and Participants: This is a case report and a review of the relevant literature. A 55-year-old woman presented to our clinic with a history of paroxysmal atrial fibrillation, hypertension, and mild mitral valve prolapse. The patient developed atrial fibrillation 3 days after receiving a COVID-19 vaccine. She was diagnosed with moderate-to-severe tricuspid regurgitation and severe mitral regurgitation, and underwent valve repair surgery. To obtain relevant articles (December 2020 through August 2022), we searched the following key words on PubMed: atrial fibrillation and COVID-19 vaccination.Results: A total of 5 relevant case reports were identified. COVID-19 vaccination led to arrhythmia, including atrial fibrillation, within 14 days.Conclusions and Relevance: Cases of patients developing arrhythmia after COVID-19 vaccination have been increasingly reported. Although the underlying mechanism remains unclear, we hypothesize that mRNA vaccination may lead to arrhythmia and associated valve diseases. Thus, before administering mRNA-1273 vaccines to patients with a history of valvular heart disease or atrial fibrillation, the patients' cardiologists must be consulted.Keywords: atrial fibrillation, valvular heart disease, COVID-19 vaccination, case report